Actitudes hacia la matemática y resolución de problemas en estudiantes de segundo de secundaria de la Institución Educativa N° 64479 Pastor Valencia Peña Bilingüe Intercultural Ramón Castilla, Caballococha Loreto 2022 - Almeida Sampayo, Armando (2024)
The objective of the study was to determine the relationship between attitudes towards mathematics, its dimensions and problem solving in second-year high school students at the I.E. 64479 Pastor Valencia Peña Bilingüe Intercultural, Ramón Castilla 2022. The study applied the quantitative approach of correlational scope and a non-experimental cross-sectional design. It included 50 students as a population and a sample to whom they applied the attitude scale towards mathematics and the problem-solving questionnaire previously validated by three experts. The study concluded that there is a moderate relationship between the attitude towards mathematics and problem solving in the second year high school students of the educational institution analyzed. According to the results of the general hypothesis test and the non-parametric Kendall's Tau-B statistic (p-value <0.001<α=0.05 and τ=0.476).